ANALYSIS OF ENVIRONMENTAL FACTORS ON HUMAN SPERM VIABILITY IN MODERN CLINICAL REPRODUCTION LABORATORY - Rizkiawati, Reza; Ernawati (Jurnal Medicare, 2025)
This study discusses the main influence of environmental factors on sperm viability in modern clinical reproductive laboratories, which is a crucial component in successful fertilization because only live and good quality sperm are capable of fertilizing an egg. Sperm are known to be very sensitive to environmental disturbances. Based on a review of the latest scientific literature (2020–2025), this study emphasizes the importance of maintaining the incubation temperature at 37°C, the pH of the culture medium between 7.2–7.4, and regulating the concentration of CO₂ (5–7%) and O₂ (5%) gases in order to create optimal culture conditions. Imbalances such as temperature fluctuations, excessively high pH, the presence of volatile organic compounds (VOCs), and exposure to light—particularly blue light—have been shown to increase oxidative stress that adversely affects sperm viability. Therefore, laboratory optimization strategies such as the use of compartment incubators, automated CO₂ regulation systems, fast and gentle sample handling, and protection from excessive light exposure are essential to enhance the success of assisted reproductive (ART) technologies such as IVF and ICSI.